OmicsVolcano: Software for intuitive visualization and interactive exploration of high-throughput biological data - Kuznetsova, I.; Lugmayr, A.; Rackham, Oliver; Filipovska, Aleksandra (2021)
Advances in omics technologies have generated exponentially larger volumes of biological data; however, their analyses and interpretation are limited to computationally proficient scientists. We created OmicsVolcano, an interactive open-source software tool to enable visualization and exploration of high-throughput biological data, while highlighting features of interest using a volcano plot interface. In contrast to existing tools, our software and user-interface design allow it to be used without requiring any programming skills to generate high-quality and presentation-ready images.